A systematic review on antimicrobial resistance in aquaculture - Haimid, Mohd Tarmizi; Suhaimee, Syahrin; Manun, Cantira; Hurairah, Sarah Nadira; Buda, Mark (Malaysian Agricultural Research and Development Institute, 2022)
Antimicrobial-resistant bacteria have been commonly introduced into fish farming systems through animal waste or overfeeding. About 80% of antimicrobials in aquaculture are used to pick the bacteria from changeable genetic components that contain various resistance causal factors transmittable to other bacteria. This causes a detrimental change in aquatic biodiversity and organisms. This paper aims to perform a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method to study the occurrence of AMR in the aquaculture industry. The objective of this study is to facilitate further studies in the field, given this gap found in the literature. This systematic review was conducted and reported based on the PRISMA approach, and the study selection process was completed using Mendeley Desktop and Microsoft Excel. Tetracyclines, sulphonamide, penicillins and phenols are the primary antimicrobial agents, whereas shrimp has been identified to be among the top species affected by AMR. This systematic review study provides critical information related to AMR, a current issue in the aquaculture industry.